The Relationship between Chronic Energy Deficiency and the Incidence of Anemia in Female Adolescent in Stunting Locus Areas - Malonda, Nancy S.H; Sanggelorang, Yulianty; Engkeng, Sulaemana; Daslety, Vindhy; Wowiling, Majesty; Ondang , Tesalonika (Journal of Maternal and Child Health, 2024)
Background: Adolescent girls are a group that is prone to anemia, so they are at risk of giving birth to stunted children. This study aims to analyze the factors most associated with the incidence of anemia in adolescent girls in the stunting locus area. Subjects and Method: This was a cross sectional study conducted in Patokaan Village, North Minahasa Regency, North Sulawesi. A total of 50 adolescent girls were selected in this study. The dependent variable was anemia. The independent variables were nutritional status, Chronic Energy Deficiency (CED), nutrient intake (Fe, protein, vitamin C), body perception (Body Image), nutritional knowledge, and menstrual patterns based. The variables studied were anemia based on laboratory examination, nutritional status according to BMI/A and CED using anthropometric methods, nutrient intake (Fe, protein, vitamin C) using 24-hour recall, body perception (Body Image), nutritional knowledge, and menstrual patterns based on questionnaire interviews. Fisher's Exact Test was used for bivariate analysis and logistic regression for multivariate analysis. Results: Adolescent girls with CED have a 5.21 times risk of experiencing anemia compared to those without CED, and this result was statistically significant (aOR= 5.21; 95% CI= 1.01 to 26.83; p = 0.048). Conclusion: CED is associate with anemia in adolescent girls in the stunting locus area. This study is expected to be useful for the North Minahasa District Health Office as input for policy makers, planning, and implementing public health nutrition programs.